Misaligned Gas Acquisition as a Formation Pathway of S0 Galaxies - Zhou, Yuren; Chen, Yanmei; Shi, Yong; Gu, Qiusheng; Wang, Junfeng; Bizyaev, Dmitry (The Astrophysical journal, 2024)
We analyze a sample of 753 S0 galaxies from the MPL-10 of Mapping Nearby Galaxies at Apache Point Observatory survey and investigate the gas–star kinematic misalignment and merger remnant fraction in galaxies with different morphological types. The misalignment fraction in S0s is the highest among all the morphological types for both young (global D n 4000 < 1.6, ∼15%) and old (global D n 4000 > 1.6, ∼10%) galaxies. We compare the properties of misaligned S0s with other types of galaxies, finding the following: (i) misaligned S0s and misaligned spirals have higher bulge luminosity, higher bulge-to-total light ratio, and larger Sérsic index compared to spirals; (ii) the misaligned S0s have lower bulge luminosity M r and smaller bulge size than merger remnant S0s, while aligned S0s have the widest coverage for these parameter distributions, which are overlapped with both misaligned S0s and merger remnant S0s; (iii) misaligned S0s have lower stellar mass M * and more isolated environment than aligned S0s and merger remnant S0s; and (iv) the young misaligned S0s have positive D n 4000 radial gradient, while the aligned S0s and merger remnant S0s show negative D n 4000 radial gradient. Combining all these observational results, we suggest misaligned gas acquisition as another efficient formation pathway for S0 galaxies. The redistribution of gas angular momentum during gas–gas collision between accreted and preexisting gas leads to gas inflow and the growth of the bulge component, while the lack of cold gas at the outskirts leads to fading of spiral arms.